The Effect of Audit Fee, Audit Tenure, Client Firm Size, and Financial Distress on Auditor Switching in Property and Real Estate Companies - Annabell Rose Tania; Susanto Salim (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of audit fee, audit tenure, client firm size, and financial distress on auditor switching among property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research is motivated by the importance of understanding the factors that drive companies to change auditors, which may reflect managerial decision-making related to audit quality and financial credibility. A quantitative descriptive method was employed using secondary data obtained from audited annual financial reports. The sample was determined through purposive sampling, while data analysis was conducted using SPSS version 25. The findings reveal that audit fee, audit tenure, and client firm size do not have a significant effect on auditor switching. In contrast, financial distress shows a significant positive effect, indicating that companies facing financial difficulties are more likely to switch auditors as an effort to enhance the credibility of their financial statements. These results suggest that financial pressure plays a more decisive role than auditor-related attributes in influencing auditor replacement within the property and real estate sector. Overall, the study contributes to the literature on auditing and corporate governance by providing empirical evidence from emerging markets, and it offers practical insights for stakeholders regarding the dynamics of auditor–client relationships in the context of financial distress.